Relación entre factores socioeconómicos y dietarios con el estado nutricional en niños del Centro Adventista de Prevención en Villa María del Triunfo, 2008 - Rómulo Hernán Ccanahuire Curasi (2019)
Purpose: To determine the relationship between socio-economic and dietary factors with the nutritional condition inchildren at the Villa María del Triunfo Adventist Center, 2008. Methodology: The present research was a descriptive,correlational, cross-section study. The sample for the study was selected from a population of ninety-nine children,through a probability sampling, randomly systematic holding a total of 60 children. The instrument applied by thestudy was a questionnaire: the socio-economic factor with 19 items, and non-healthy food consumption with 13items. In the same way a 24 hour reminder and an anthropometric assessment formulary were used. The informationanalysis was performed through: the WHO Anthro Plus software for nutritional evaluation; and for the food chemicalcomposition, the Nutrisoftware Professional was used. The statistical SPSS program, version 16 was employed fordata processing. The variables correlation was measured through the Pearson Chi-square (X2) tests. Results: from73.33% of families with unsatisfied basic needs, all qualified for malnutrition, overweight or obesity; the mostvulnerable age is between seven and eight years of age, 71.67%. On the other hand, it was found that more thanthe fourth part of children with delayed growth 30%, overweight, and 36.67%obese, qualified for under-adequateand over-adequate diet respectively, where the majority of girls, 81.51%, presented non-healthy food consumption.The tests reported a significant relation (p=0.000) among the variables. Conclusion: there is a relationship betweenthe socio-economic and dietary factors with the nutritional condition in children at the Villa María del TriunfoPrevention Adventist Center, 2008.